Manganese oxide on fluorine-doped SnO2 inverse opal frame as pseudocapacitor electrodes. Issue 14 (1st October 2020) - Kim, Kyungbae; Arunachalam, Maheswari; Seo, Hyungeun; Kang, Soon Hyung; Kim, Jae-Hun
Abstract: We present F-doped SnO2 (FTO) inverse opal (IO) core-MnO shell-structured electrodes for supercapacitors. The FTO IO core structure was prepared using a polymer-templating method, and the pseudocapacitive MnO material was electrodeposited on the surface to induce faradaic charge storage reactions. The synthesized material and its microstructure were characterized by X-ray diffraction, electron microscopy, and X-ray photoelectron spectroscopy. Cyclic voltammetry was used to investigate the electrochemical reaction kinetics of the MnO-FTO IO electrode. MnO-FTO planar electrodes were adopted as control samples. The electrode exhibited superior reaction kinetics which could be ascribed to its microstructure. The conductive FTO IO core provided electronic pathways, and its three-dimensional ordered mesoporous structure helped achieve fast electrolyte penetration. Additionally, the MnO shell material's high surface areas permitted rapid pseudocapacitive faradaic reactions. Up to 40, 000 cycles of galvanostatic charge-discharge cycling were performed. The capacitance was well maintained over the extremely long cycles due to the mechanical stability of the MnO shell material.